Identification of a novel subunit of respiratory complex I from Thermus thermophilus - Hinchliffe, Philip; Carroll, Joe D; Leonid Sazanov (Biochemistry)
The hydrophilic domain (peripheral arm) of the proton-translocating NADH:quinone oxidoreductase (complex I) from the thermophilic organism Thermus thermophilus HB8 has been purified and characterized. The subcomplex is stable in sodium dodecyl sulfate up to 80 °C. Of nine iron-sulfur clusters, four to five (one or two binuclear and three tetranuclear) could be detected by EPR in the NADH-reduced enzyme. The preparation consists of eight different polypeptides. Seven of them have been positively identified by peptide mass mapping and N-terminal sequencing as known hydrophilic subunits of T. thermophilus complex I. The eighth polypeptide copurified with the subcomplex at all stages, is strongly associated with the other subunits, and is present in crystals of the subcomplex, used for X-ray data collection. Therefore, it has been identified as a novel complex I subunit and named Nqo15. It is encoded in a locus separate from the nqo operon, containing the 14 other known complex I genes. ORFs encoding Nqo15 homologues are present in the genomes of the closest relatives of T. thermophilus. Our data show that, contrary to previous assumptions, bacterial complex I can contain proteins in addition to a "core" complement of 14 subunits.

Evidence for Efimov quantum states in an ultracold gas of caesium atoms - Kraemer, Tobias; Mark, Michael; Waldburger, Philipp; Danzl, Johann G; Chin, Cheng; Engeser, Bastian; Lange, Adam; Pilch, Karl; Jaakkola, Antti; Nägerl, Hanns; Grimm, Rudolf (Nature)
Systems of three interacting particles are notorious for their complex physical behaviour. A landmark theoretical result in few-body quantum physics is Efimov\'s prediction1,2 of a universal set of bound trimer states appearing for three identical bosons with a resonant two-body interaction. Counterintuitively, these states even exist in the absence of a corresponding two-body bound state. Since the formulation of Efimov\'s problem in the context of nuclear physics 35 years ago, it has attracted great interest in many areas of physics3-8. However, the observation of Efimov quantum states has remained an elusive goal3,5. Here we report the observation of an Efimov resonance in an ultracold gas of caesium atoms. The resonance occurs in the range of large negative two-body scattering lengths, arising from the coupling of three free atoms to an Efimov trimer. Experimentally, we observe its signature as a giant three-body recombination loss9,10 when the strength of the two-body interaction is varied. We also detect a minimum 9,11,12 in the recombination loss for positive scattering lengths, indicating destructive interference of decay pathways. Our results confirm central theoretical predictions of Efimov physics and represent a starting point with which to explore the universal properties of resonantly interacting few-body systems7. While Feshbach resonances13,14 have provided the key to control quantum-mechanical interactions on the two-body level, Efimov resonances connect ultracold matter15 to the world of few-body quantum phenomena.

Experimental evidence for Efimov quantum states - Nägerl, Hanns; Kraemer, Tobias; Mark, Michael; Waldburger, Philipp; Danzl, Johann G; Engeser, Bastian; Lange, Adam; Pilch, Karl; Jaakkola, Antti; Chin, Cheng; Grimm, Rudolf
Three interacting particles form a system which is well known for its complex physical behavior. A landmark theoretical result in few-body quantum physics is Efimov\'s prediction of a universal set of weakly bound trimer states appearing for three identical bosons with a resonant two-body interaction [1, 2]. Surprisingly, these states even exist in the absence of a corresponding two-body bound state and their precise nature is largely independent of the particular type of the two-body interaction potential. Efimov\'s scenario has attracted great interest in many areas of physics; an experimental test however has not been achieved. We report the observation of an Efimov resonance in an ultracold thermal gas of cesium atoms [3]. The resonance occurs in the range of large negative two-body scattering lengths and arises from the coupling of three free atoms to an Efimov trimer. We observe its signature as a giant three-body recombination loss when the strength of the two-body interaction is varied near a Feshbach resonance. This resonance develops into a continuum resonance at non-zero collision energies, and we observe a shift of the resonance position as a function of temperature. We also report on a minimum in the recombination loss for positive scattering lengths, indicating destructive interference of decay pathways. Our results confirm central theoretical predictions of Efimov physics and represent a starting point from which to explore the universal properties of resonantly interacting few-body systems.

Analysis of human faces using a measurement-based skin reflectance model - Weyrich, Tim; Matusik, Wojciech; Pfister, Hanspeter; Bernd Bickel; Donner, Craig; Tu, Chien; McAndless, Janet M; Lee, Jinho; Ngan, Addy; Jensen, Henrik W; Groß, Markus S
We have measured 3D face geometry, skin reflectance, and subsurface scattering using custom-built devices for 149 subjects of varying age, gender, and race. We developed a novel skin reflectance model whose parameters can be estimated from measurements. The model decomposes the large amount of measured skin data into a spatially-varying analytic BRDF, a diffuse albedo map, and diffuse subsurface scattering. Our model is intuitive, physically plausible, and - since we do not use the original measured data - easy to edit as well. High-quality renderings come close to reproducing real photographs. The analysis of the model parameters for our sample population reveals variations according to subject age, gender, skin type, and external factors (e.g., sweat, cold, or makeup). Using our statistics, a user can edit the overall appearance of a face (e.g., changing skin type and age) or change small-scale features using texture synthesis (e.g., adding moles and freckles). We are making the collected statistics publicly available to the research community for applications in face synthesis and analysis.

Analysis of human faces using a measurement-based skin reflectance model - Weyrich, Tim; Matusik, Wojciech; Pfister, Hanspeter; Bernd Bickel; Donner, Craig; Tu, Chien; McAndless, Janet M; Lee, Jinho; Ngan, Addy; Jensen, Henrik W; Groß, Markus S (ACM Transactions on Graphics)
We have measured 3D face geometry, skin reflectance, and subsurface scattering using custom-built devices for 149 subjects of varying age, gender, and race. We developed a novel skin reflectance model whose parameters can be estimated from measurements. The model decomposes the large amount of measured skin data into a spatially-varying analytic BRDF, a diffuse albedo map, and diffuse subsurface scattering. Our model is intuitive, physically plausible, and - since we do not use the original measured data - easy to edit as well. High-quality renderings come close to reproducing real photographs. The analysis of the model parameters for our sample population reveals variations according to subject age, gender, skin type, and external factors (e.g., sweat, cold, or makeup). Using our statistics, a user can edit the overall appearance of a face (e.g., changing skin type and age) or change small-scale features using texture synthesis (e.g., adding moles and freckles). We are making the collected statistics publicly available to the research community for applications in face synthesis and analysis.

Processing and editing of faces using a measurement-based skin reflectance model - Bernd Bickel; Weyrich, Tim; Matusik, Wojciech; Pfister, Hanspeter; Donner, Craig; Tu, Chien; McAndless, Janet M; Lee, Jinho; Ngan, Addy; Jensen, Henrik W; Groß, Markus S

The density of rational points on non-singular hypersurfaces, II - Timothy Browning; Heath-Brown, Roger; Starr, Jason M (Proceedings of the London Mathematical Society)
For any integers d,n ≥2, let X ⊂ Pn be a non‐singular hypersurface of degree d that is defined over the rational numbers. The main result in this paper is a proof that the number of rational points on X which have height at most B is O(Bn − 1 + ɛ), for any ɛ > 0. The implied constant in this estimate depends at most upon d, ɛ and n. 2000 Mathematics Subject Classification 11D45 (primary), 11G35, 14G05 (secondary).

Predissociation of the N+2(C 2Σ+u) state observed via C 2Σ+u → X 2Σ+g fluorescence after resonant 1s−1π* excitation of N2 molecule - Ehresmann, Arno; Werner, Lutz; Klumpp, Stefan; Demekhin, Ph V; Mikhail Lemeshko; Sukhorukov, V. L; Schartner, Karl H; Schmoranzer, Hans P (Journal of Physics B: Atomic, Molecular and Optical Physics)
Predissociation of the N+2 C 2Σ+u(v') vibrational levels with v' ≥ 3 was observed via dispersed C 2Σ+u → X 2Σ+g fluorescence in the spectral range of 165–208 nm after resonant 1s−1π*(vr) excitation of N2 and its subsequent autoionization into the N+2 C state. This range is dominated by lines in atomic nitrogen, by overlapped C 2Σ+u(v') → X 2Σ+g(v'') vibrational band sequences with Δv = const and broad unresolved band systems (D, (2))2Πg(v') → A2Πu(v'') in the N+2 molecular ion. With very high fluorescence resolution of about 0.1 nm FWHM individual C 2Σ+u(v') → X 2Σ+g(v'') vibrational bands have been resolved. Calculation of the observed fluorescence spectra by taking into account predissociation and molecular rotation describes well the shape of both individual vibrational bands C 2Σ+u(v') → X 2Σ+g(v'') and the whole band system.

Studying the N+2(C2Σ+u → X2Σ+g) fluorescence excited via the 1s−1π* resonance - Ehresmann, Arno; Werner, Lutz; Klumpp, Stefan; Lucht, S; Schmoranzer, Hans P; Mickat, Sascha; Schill, Rüdiger H; Schartner, Karl H; Demekhin, Philipp; Mikhail Lemeshko; Sukhorukov, Victor L (Journal of Physics B: Atomic, Molecular and Optical Physics)
Fluorescence from fragments formed after the de-excitation of the N*2(1s−1π*) resonance has been measured in the spectral range of 135–190 nm. This range is dominated by lines in atomic nitrogen and lines formed by overlapping C2Σ+u(v') → X2Σ+g(v'') bands with Δv = const in the N+2 molecular ion which result from the spectator Auger decays of the N*2(1s−1π*(vr)) resonances. Ab initio calculations of the corresponding potential curves and transition probabilities showed that the observed irregular intensity dependence of the C2Σ+u(v') → X2Σ+g(v'')(Δv = const) fluorescence lines on the vibrational quantum number vr is due to transitions between vibrational levels during the reaction N2(v0 = 0)→ N*2(1s−1π*(vr)) Longrightarrow C2Σ+u(v') → X2Σ+g(v'').

Temperature dependent XAFS studies of local atomic structure of the perovskite-type zirconates - Vedrinskiǐ, Rostislav V; Nazarenko, Elena S; Mikhail Lemeshko; Nassif, Vivian M; Proux, Olivier; Novakovich, Alexander A; Joly, Yves (Physical Review B - Condensed Matter and Materials Physics)
Temperature dependent preedge and extended x-ray absorption fine structure measurements at the Zr K edge for the perovskite-type zirconates Pb Zr0.515 Ti0.485 O3 (PZT), PbZr O3 (PZ), and BaZr O3 are performed. To carry out a more accurate study of the weak reconstruction of the local atomic structure we employed a combination of two techniques: (i) analysis of the preedge fine structure, and (ii) analysis of the Fourier transform of the difference between χ (k) functions obtained at different temperatures. A detailed investigation of local atomic structure in the cubic phase for all the crystals is also performed. It is shown that neither the displacive nor the order-disorder model can describe correctly the changes of local atomic structure during phase transitions in PZ and PZT. A spherical model describing the local atomic structure of perovskite-type crystals suffering structural phase transitions is proposed.

The density of rational points on non-singular hypersurfaces, I - Timothy Browning; Heath-Brown, Roger (Bulletin of the London Mathematical Society)
For any n≥3, let F ∈ Z[X0,...,Xn ] be a form of degree d *≥5 that defines a non-singular hypersurface X ⊂ Pn . The main result in this paper is a proof of the fact that the number N (F ; B) of Q-rational points on X which have height at most B satisfiesN (F ; B) = Od,ε,n (Bn −1+ε ), for any ε > 0. The implied constant in this estimate depends at most upon d, ε and n. New estimates are also obtained for the number of representations of a positive integer as the sum of three dth powers, and for the paucity of integer solutions to equal sums of like polynomials.*

Counting rational points on algebraic varieties - Timothy Browning; Heath-Brown, Roger; Salberger, Per (Duke Mathematical Journal)
For any N ≥ 2, let Z ⊂ ℙN be a geometrically integral algebraic variety of degree d. This article is concerned with the number Nz(B) of ℚ-rational points on Z which have height at most B. For any ε > 0, we establish the estimate NZ(B) = O d,ε,N(Bdim Z+ε), provided that d ≥ 6. As indicated, the implied constant depends at most on d, ε, and N.

Sums of arithmetic functions over values of binary forms - de la Bretèche, Régis; Timothy Browning (Acta Arithmetica)
This paper is concerned with the average order of certain arithmetic functions, as they range over the values taken by binary forms.

Ground-state energy of a dilute Fermi gas - Lieb, Élliott H; Robert Seiringer; Solovej, Jan P

One-dimensional behavior of dilute, trapped Bose gases in traps - Robert Seiringer; Lieb, Élliott H; Yngvason, Jakob

Derivation of the Gross-Pitaevskii equation for rotating Bose gases - Lieb, Élliott H; Robert Seiringer (Communications in Mathematical Physics)
We prove that the Gross-Pitaevskii equation correctly describes the ground state energy and corresponding one-particle density matrix of rotating, dilute, trapped Bose gases with repulsive two-body interactions. We also show that there is 100% Bose-Einstein condensation. While a proof that the GP equation correctly describes non-rotating or slowly rotating gases was known for some time, the rapidly rotating case was unclear because the Bose (i.e., symmetric) ground state is not the lowest eigenstate of the Hamiltonian in this case. We have been able to overcome this difficulty with the aid of coherent states. Our proof also conceptually simplifies the previous proof for the slowly rotating case. In the case of axially symmetric traps, our results show that the appearance of quantized vortices causes spontaneous symmetry breaking in the ground state.

A correlation estimate for quantum many-body systems at positive temperature - Robert Seiringer (Reviews in Mathematical Physics)
We present an inequality that gives a lower bound on the expectation value of certain two-body interaction potentials in a general state on Fock space in terms of the corresponding expectation value for thermal equilibrium states of non-interacting systems and the difference in the free energy. This bound can be viewed as a rigorous version of first-order perturbation theory for many-body systems at positive temperature. As an application, we give a proof of the first two terms in a high density (and high temperature) expansion of the free energy of jellium with Coulomb interactions, both in the fermionic and bosonic case. For bosons, our method works above the transition temperature (for the non-interacting gas) for Bose-Einstein condensation.

The thermodynamic pressure of a dilute Fermi gas - Seiringer, Robert (Communications in Mathematical Physics)
We consider a gas of fermions with non-zero spin at temperature T and chemical potential μ. We show that if the range of the interparticle interaction is small compared to the mean particle distance, the thermodynamic pressure differs to leading order from the corresponding expression for non-interacting particles by a term proportional to the scattering length of the interparticle interaction. This is true for any repulsive interaction, including hard cores. The result is uniform in the temperature as long as T is of the same order as the Fermi temperature, or smaller.

Lieb-Thirring inequalities for Schrödinger operators with complex-valued potentials - Frank, Rupert L; Laptev, Ari; Lieb, Élliott H; Robert Seiringer (Letters in Mathematical Physics)
Inequalities are derived for power sums of the real part and the modulus of the eigenvalues of a Schrödinger operator with a complex-valued potential.

Dilute, trapped Bose gases and Bose-Einstein condensation - Robert Seiringer (Large Coulomb Systems)
The recent experimental success in creating Bose-Einstein condensates of alkali atoms, honored by the Nobel prize awards in 2001 [1,5], led to renewed interest in the mathematical description of interacting Bose gases.